Innovation in Digital Media-Based Islamic Teaching and Learning: A Study of Senior High Schools in Nigeria - Jibril, Ayuba Olaniyi; S, Abdulkadir; L. I, Ja’afar; A. A., Mohammed (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
The main aim of this study was to examine the innovation in digital media-based Islamic teaching and learning: A study of senior high schools in Nigeria. This study critically investigated the use of digital devices to teach Islamic studies education and the challenges militating against using digital devices for teaching and learning Islamic studies education among senior high schools in Nigeria. A descriptive survey research design was employed for the study. A simple random sampling technique was used to select 503 respondents as the sample size for this study. Researchers designed a questionnaire, tagged “Questionnaire on the Integration of Digital Tools for Teaching and Learning Islamic Studies in the Digital Era (QIDTTLISDE),” which was used to elicit information from the respondents for the study. The reliability of the instrument was assessed with a reliability index of 0.77. The study's findings revealed that Zoom, Google Meet, Facebook, LinkedIn, Coursera, TutorMe, Chegg Tutors, Udemy, and YouTube are digital tools used to teach Islamic studies among senior high schools in Nigeria. The study also revealed that the digital tools are to a very great extent used for learning and teaching of Islamic studies among high school students of Islamic studies in Nigeria and that limited accessibility and network connection, schools with insufficient instructional software, lack of technical expertise, unreliable power supply, lack of teachers’ competency and poor maintenance of digital tools in educational institutions as about material and non-material conditions are the challenges militating against the use of digital tools among senior high schools in Nigeria. It is concluded that using digital tools for teaching and learning of Islamic studies among senior high schools in Nigeria significantly enhanced the academic performance of senior high school students and simplified the teaching and learning process. Furthermore, the study recommended that the government provide more digital tools for teaching and learning Islamic studies in high schools in Nigeria